Market Reaction To The Announcement Of The European Union Coal Embargo On Coal Import From Russia In Other Exporting Countries - Rahayu, Nabila (Integrasi Sains Media, 2023)
European Union announced the fifth sanctions package against Russia in April 2022, a ban on coal imports from Russia to the EU. The EU seeks to find an alternative country to fulfil the country's demand for coal commodities. In this case, South Africa experienced the highest increase in coal supply volume to European countries compared to other coal suppliers. The increase in coal import volume makes South Africa the possible alternative to fulfil coal demand for European countries. Therefore, as there is a huge increase in supply volume, the author intends to investigate whether or not there is an impact on the stock market in the alternate country. This research analyses the market reaction to the EU coal embargo on coal stocks as reflected in abnormal return and trading volume activity in the alternative country, South Africa. The analysis uses the stock price and volume of listed coal companies in South Africa before and after the announcement of the EU coal embargo. The researcher used an event study approach with an event window of 10 days before and 10 days after the announcement to calculate the abnormal return and trading volume activity, while the estimated period was set to be 100 days to calculate the expected return. The step analysis conducted in this study is to test the normality of the data first and then assess the hypothesis testing. This study's results show no significant difference in abnormal return and trading volume activity before and after the announcement. This result might happen because the EU had given a signal by proposing a far-reaching ban across Russia's energy sector through the fourth sanctions; thus, investors might have predicted the event in advance.